THE ROLE OF HUMAN PAPILLOMAVIRUS IN DEVELOPMENT OF OROPHARYNGEAL CANCER - A. I. Stukan; V. N. Bodnya; E. V. Dulina; A. A. Leonov; V. I. Aleksandrov (Кубанский научный медицинский вестник, 2016)
This article provides review of foreign literature on the problem of HPV-associated oropharyngeal cancer incidence. Epidemiological researches demonstrate increase of incidence of oropharyngeal squamous cell carcinoma (OPSCC) especially among white men of middle age. Such growth of oropharyngeal cancer incidence is associated with human papilloma virus type 16 (HPV 16). The p16 - protein expression is the marker of HPV DNA integration into human nuclear DNA. It is suggested that detection of tumor HPV-status can predict prognosis and develop preventive measures.